Semifluorinated Alkylphosphonic Acids Form High-Quality Self-Assembled Monolayers on Ag-Coated Yttrium Barium Copper Oxide Tapes and Enable Filamentization of the Tapes by Microcontact Printing - Park, Chul Soon (Langmuir : the ACS journal of surfaces and colloids, 2016)
A custom-designed semifluorinated phosphonic acid, (9,9,10,10,11,11,12,12,13,13,14,14,15,15,16,16,16-heptadecafluorohexadecyl)phosphonic acid (F8H8PA), and a normal hexadecylphosphonic acid (H16PA) were synthesized and used to generate self-assembled monolayers (SAMs) on commercially available yttrium barium copper oxide (YBCO) tapes. In this study, we wished to evaluate the effectiveness of these monolayer films as coatings for selectively etching YBCO. Initial films formed by solution deposition and manual stamping using a non-patterned polydimethylsiloxane stamp allowed for a comparison of the film-formation characteristics. The resulting monolayers were characterized by X-ray photoelectron spectroscopy (XPS), contact angle goniometry, and polarization modulation infrared reflection absorption spectroscopy (PM-IRRAS). To prepare line-patterned (filamentized) YBCO tapes, standard microcontact printing (μ-CP) procedures were used. The stamped patterns on the YBCO tapes were characterized by scanning electron microscopy (SEM) before and after etching to confirm the effectiveness of the patterning process on the YBCO surface and energy-dispersive X-ray spectroscopy (EDX) to obtain the atomic composition of the exposed interface